The vermian-crest angle: a prediction model for foetal cystic posterior fossa anomalies - Spinelli, Marialuigia; Amylidi-Mohr, Sofia; Surbek, Daniel; Heling, Kai-Sven; Scheier, Matthias; Pomar, Leo; Baud, David; Raio, Luigi (Frontiers in Neuroscience, 2025)
BackgroundAccurate categorisation of the upward rotation of the foetal cerebellar vermis continues to pose diagnostic challenges in prenatal medicine. Recently, a new parameter of the posterior fossa (PF), known as the vermian-crest angle (VCA), has been evaluated using three-dimensional ultrasound (3D-US) and prenatal magnetic resonance imaging (MRI).ObjectiveThis study aimed to evaluate the performance of the VCA in categorizing PF anomalies using 3D-US and to determine its level of agreement with MRI.Study designWe conducted a cohort study involving confirmed cases of PF anomalies. We measured the VCA using 3D-US and compared our data with previously published reference values obtained through both 3D-US and MRI. For statistical analysis, we employed univariate analysis of variance (ANOVA) followed by Tukey’s post-hoc test, receiver operating characteristic (ROC) curve analysis, and the intraclass correlation coefficient (ICC).ResultsWe identified 53 foetuses at a mean gestational age (GA) of 24.5 (SD 5.45) weeks with Blake’s pouch cyst (BPC) (n = 11), Dandy–Walker malformation (DWM) (n = 9), mega cisterna magna (MCM) (n = 22), and vermian hypoplasia (VH) (n = 11). Compared to published reference values, the VCA was significantly increased in DWMs (mean 130.6°, SD 16.75°; p ≤ 0.01) and BPCs (mean 91.00°, SD 19.73°; p ≤ 0.05). A VCA > 80.1° distinguished BPCs and DWMs from other PF anomalies, while a VCA > 107° differentiated BPCs from DWMs. When comparing subgroups with published MRI data, we found good agreement between 3D-US and MRI (ICC = 0.71) (95% CI: 0.55–0.87).ConclusionThe VCA may be helpful in categorising PF anomalies using 3D-US, particularly BPC and DWM. The good agreement with MRI measurements reinforces the synergy of these tools in the diagnostic work-up.